CRITICIZING YOGYAKARTA ENVIRONMENT ON THE OFFICIAL WEBSITE OF INDONESIAN TOURISM: AN ECOLINGUISTIC STUDY - Arina Isti'anah (UIN Raden Mas Said Surakarta, 2020)
Tourism is one of the sectors which defines the identity of a country. In Indonesia, rich in culture and nature, the use website is benefited by the government to portray as well as gain profit from the tourism sites. This paper, thus, intends to discuss how the environment in Yogyakarta tourism is criticized on the website. The interest of linguistics to criticize how its usage affects the environment triggers the development of ecolinguistics. Saphir distinguishes three ecological territories: physical, economic and social. Ecological domains are exercised to present Yogyakarta on Wonderful Indonesia, the official website of Indonesian tourism. This paper observed the employment of clauses of Yogyakarta text found in the Destination Highlight on the front page of the website at www.indonesia.travel on March 31, 2019. The method applied is ecolinguistics by exercising the ideational metafunction of language proposed by Halliday's Systemic Functional Linguistics (SFL) to figure out how the website portrays the real world of Yogyakarta environment seen from the choice of process, participants and circumstances. The analysis reveals that social environment dominates the website, meaning that Yogyakarta is advertised as a carrier and attribute in terms of its culture and value. Yogyakarta, is attached to the attributes as a city with respect for values. This paper proposes criticizes to present Yogyakarta through material processes to demonstrate how local people, as well as tourists, value and engage in preserving the environment of Yogyakarta.Â